Affective outcomes during and after high-intensity exercise in outdoor green and indoor gym settings. Issue 2 (4th March 2017) - Turner, Toby Louis; Stevinson, Clare
Abstract: Outdoor exercise settings promote greater psychological well-being than synthetic equivalents, although the influence of the exercise context has not been investigated at high exercise intensities. This study compared the psychological effects of high-intensity exercise in outdoor green and indoor gym settings in 22 adult runners using a randomized repeated measures design. Affect and perceived exertion were assessed before, during, and after a 6000-m run with the second half completed at maximum effort. Perceived exertion and activation increased in a progressive manner from baseline to 6000 m, and decreased during the 10-min recovery post-run. Non-significant reductions in affective valence were observed between 3000 and 6000 m, followed by a significant increase post-run. Outcomes did not differ at any time point between the settings. This study suggested that regular runners experience positive affective responses during and after high-intensity exercise in both a natural outdoor environment and an indoor gym.